Forfatteroversigt. Navne og kontaktoplysninger om bidragydere - Pedersen, Kim Arne; Bradley, S. A. J.; Lundgreen-Nielsen, Flemming; Overgaard, Ulrik (Grundtvig-Studier, 2009)
List of authors' adresses